Agarwood Pill Enhances Immune Function in Cyclophosphamide-induced Immunosuppressed Mice - Ji, Seon Yeong; Lee, Hyesook; Hwangbo, Hyun; Kim, Min Yeong; Kim, Da Hye; Park, Beom Su; Koo, Young Tae; Kim, Jin Soo; Lee, Ki Won; Ko, Jong Cheul; Kim, Gi-Young; Bang, EunJin; et al. (Biotechnology and bioprocess engineering, 2023)
Agarwood is a resinous wood from the tree in the family Thymelaeaceae . It has been used as traditional medicine in China and Southeast Asia countries. This study was conducted to evaluate the potential of agarwood pill (AP) as a supplement to enhance immune function. In this study, immunity-enhancing activity was demonstrated in BALB/c male mice administered with AP for 10 days after intraperitoneal injection of cyclophosphamide (CPA). Results demonstrated that AP supplementation ameliorated spleen index and body weight changes of CPA-injected mice by increasing the proliferation of T- and B-lymphocytes as well as the activity of natural killer cells. Analysis of spleen-derived lymphocytes showed that counts of CD4 + and CD8 + T-cells were slightly recovered in the spleen of mice treated with a high dosage of AP. Serum levels of immune-related cytokines of tumor necrosis factor-α were notably restored after AP administration. In addition, serum levels of immunoglobulin (Ig) M and IgG were recovered by AP administration at a medium dosage. Furthermore, in analysis of ex vivo bone marrow-derived macrophages and dendritic cells, counts of immune-related interleukin-12, major histocompatibility complex (MHC)-I, MHC-II, CD80, and CD86 were significantly increased by AP treatment in concentration-dependent manner. This study provides reference data for the development of AP as a supplementation to enhance human immune function.